Moral Ideal Through Islamic Religious Education: Purpose, Concept and Implementation - Ahmad Irfan; Siti Shofiyah; Ummah Karimah (Future Science, 2023)
The system of regulating a relationship not only between humans and God, between humans and humans, but also between humans and their envi-ronment, this is what is called Islam as a universal religion. When it comes to moral teachings, such as Islamic religious education, Muslims frequently refer to the Qur'an and the prophet's hadith in their behavior. A descriptive qualitative method of library research is used in this study. The main source of data for this study is academic literature on Islamic and moral religious education, specifically books and periodicals. Data collection techniques in this study the author used the literature review method. While the data analysis technique the author uses data reduction tech-niques, data presentation and conclusion drawing. This article discusses moral ideals. In other words, the extent to which the idealistic level of a moral allows a learner in his daily life. So here, social life can build civiliza-tion and progress a nation. A learner's morals can be developed in the edu-cational system at school through Islamic religious education in order to accomplish this purpose. Additionally, in relation to the idea of Islamic mo-rality as taught in Islamic religious education. Human resources are re-quired in educational organizations in order to accomplish the goal of achieving a moral ideal through Islamic religious education. Services, the application or implementation in each subject, is one of the manifestations of a systematic activity on how to plan an activity that always applies moral ideals.